Assessing structural efficiency: a study of gravity balanced cable-stay bridges. Issue 1 (19th December 2018) - Croll, James G. A.
Abstract : The past few decades have witnessed a rapid increase in the role of the architect in the design of the once sacrosanct area of engineering – bridge design. Reasons for this relative decline in the engineer's role are many and varied, but must include the overemphasis on detailed analysis at the expense of understanding and creative design in engineering courses and the alarming reduction in structural education from engineering courses. With software now readily available to perform detailed structural analysis there is an opportunity to rebalance engineering courses towards much greater emphasis on understanding and design involving new approaches to analysis that can directly assist rational decision making. This paper demonstrates how simple, physically based, analyses can aid rational decision making in bridge design and suggests that such approaches could play a wider role in engineering courses. By way of illustration, these approaches are applied to the iconic, much copied, gravity balanced cable-stay Alamillo Bridge designed by Calatrava. This example also demonstrates the inefficiency of this bridge form and shows how such approaches, applied at an early design stage, could help bring rational engineering judgement back into bridge design at a time when the planet can ill afford such unsustainable solutions.